The Influence of Inclusive Education on the Mathematics Achievement of Students with Intellectual Disabilities - Riski, Karunia Ilahi; Asrorul, Mais; endra, priawasana; Lailil, Aflahkul Yaum (Universitas Veteran Bangun Nusantara, 2025)
This study investigated the differences in mathematics achievement among elementary school students with intellectual disabilities (IDs) enrolled in inclusive classes and those in special schools (SLB). Mathematics achievement was assessed at the beginning and end of the academic year in two groups: students in inclusive classes (n = 44) and in special schools (n = 56). The findings revealed that students with IDs in inclusive settings demonstrated slightly greater improvement in mathematics achievement over nine months compared to their peers in special schools. More students with very low mathematics skills were concentrated in special schools and showed minimal progress, while those with some numeracy abilities were more frequently found in inclusive classes. To account for differences in age, IQ, and prior achievement, a matched sample (n = 44) was used for regression analysis, which confirmed a small positive effect of the inclusive setting on learning gains. These findings suggest that inclusive education can provide a more supportive and stimulating learning environment that promotes academic development for students with IDs. The study holds practical implications for educational policymakers by highlighting the potential of inclusive settings to enhance learning outcomes for children with disabilities, supporting the need for more inclusive practices and tailored support systems within general education classrooms.